2023
DOI: 10.3389/fimmu.2023.1274241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sublingual versus subcutaneous immunotherapy in children with allergic rhinitis: a systematic review and meta-analysis

Jiumei Yang,
Sihong Lei

Abstract: AimTo systematically compare the efficacy and safety of subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) in children with allergic rhinitis (AR).MethodsPubMed, Embase, Cochrane Library, and Web of Science were searched from inception to March 2, 2023. Outcomes included symptom scores (SSs), medication scores (MSs), symptom and medication scores (SMSs), new sensitizations, development of asthma, improvement, and treatment-related adverse events (TRAEs). The quality of the included studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Thus, Brüggenjürgen et al reported the greater efficacy (in terms of symptom reduction) and cost-effectiveness of SCIT (compared to SLIT) for grass pollen for the treatment of hay fever [ 21 ]. In contrast, Yang et al reported at least an equivalent efficacy of SLIT compared with that of SCIT in children with allergic upper airway disease and SIT for either grass pollen or HDM [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Brüggenjürgen et al reported the greater efficacy (in terms of symptom reduction) and cost-effectiveness of SCIT (compared to SLIT) for grass pollen for the treatment of hay fever [ 21 ]. In contrast, Yang et al reported at least an equivalent efficacy of SLIT compared with that of SCIT in children with allergic upper airway disease and SIT for either grass pollen or HDM [ 22 ].…”
Section: Discussionmentioning
confidence: 99%